To Raise the Polyclonal Immuno-Probe(s) and Development of Enzyme Immuno-Assay for Detection of Cross Reactivity of Alternaria brassicae and their Different Isolates - Singh, Amardeep; Shukla, Gyanika; Gaurav, Shailendra Singh (International Journal of Scientific Research in Biological Sciences, 2019)
Alternaria brassicae is a fungus commonly found in South-East Asia, is one of the most common plant pathogenic fungi in Brassica crops. Its toxic activities have been proved. Hence, a sensitive, rapid and inexpensive screening test to detect Alternaria brassicae in agricultural commodities is necessary to protect Brassica crops. In the present study, the proteins of Alternaria brassicae were isolated, prepared, characterized and used as an antigen to raise polyclonal antibodies (pAbs) against it. Rabbits were immunized by the antigen in combination with Freund’s adjuvant. Immuno blotting analysis was performed to determine antibody specificity towards the antigen. Hybridoma supernatants were screened by enzyme-linked immuno- sorbent assay (ELISA), dot-blot and slot-blot tests which confirmed the presence of specific Antigen-Antibody interactions among pAbs and Alternaria brassicae antigens. It was observed that most of the pAbs cross-reacted with the fungi. It was concluded that development of highly specific monoclonal antibodies (mAb) against the specific strain of Alternaria brassicae can be done in near future. It will be used for the disease diagnostic and identification of infection level.